Impact of total gastrectomy plus perioperative PD-1 inhibitors on survival in locally advanced gastric cancer - Zhang, Fan; Huang, Min (Frontiers in Oncology, 2026)
BackgroundThe prognosis for locally advanced gastric cancer (LAGC) remains suboptimal with standard perioperative chemotherapy. Integrating PD-1 inhibitors into this regimen is a promising strategy requiring further validation.ObjectiveTo evaluate the efficacy and safety of total gastrectomy plus perioperative PD-1 inhibitor (Sintilimab) in the management of locally advanced gastric cancer (LAGC).MethodsIn this retrospective cohort study, 200 patients with LAGC undergoing total gastrectomy (January 2021 - November 2022) were categorized based on treatment received into an experimental group (perioperative sintilimab + XELOX, n=100) and a control group (perioperative XELOX alone, n=100).ResultsThe experimental group demonstrated the markedly higher rates of R0 resection rate (97%: 90%, P < 0.05), pCR (25%: 10%, P < 0.05), and MPR (35%: 20%, P < 0.05) as opposed to the control group. Survival analysis revealed significantly better outcomes in the experimental group: 3-year OS (48%: 30%, P = 0.009), median OS (34.7: 23.6 months, P = 0.004), 3-year DFS (40%: 25%, P = 0.001), and median DFS (30.4: 21.3 months, P = 0.007) Two groups showed no clinically relevant difference in the frequency of grade ≥3 therapy-related adverse events (56.0%: 51.0%, P > 0.05). Immune-related adverse outcomes in the experimental group were mainly grade 1–2 hypothyroidism and rash, which were relieved after symptomatic treatment.ConclusionTotal gastrectomy combined with perioperative sintilimab +XELOX regimen for LAGC significantly improves radical surgery, pathological response rate and long-term survival, with a manageable safety profile, offering a potentially effective treatment strategy.